A meta-review of patient engagement, shared decision-making, and factors influencing equity-deserving populations’ participation in clinical trials - Morgan, Tamara L.; Carroll, Kelly; Waqar, Anosha; Hudek, Natasha; Mosa, Meena; Richards, Dawn P.; Meeking, Kim; Granieri, Marisa; Smith, Maureen; Walz, Murray; Etherington, Cole; Marlin, Susan; et al. (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background Many equity-deserving populations, including those facing structural health inequities, lack support to participate in clinical trials while facing barriers to participation. Two approaches—patient engagement (PE) and shared decision-making (SDM)—can help trialists better understand and address such barriers. PE can improve the relevance of trials to silenced communities while SDM can align participation decisions among socially disadvantaged groups with their values, needs, and preferences, which may help overcome health inequities. Further, Indigenous community engagement is vital to address the effects of colonialism and promote Indigenous self-determination and health equity. The extent to which existing reviews have identified common barriers, enablers, and strategies across equity-deserving groups and discussed PE and SDM concepts is unclear. Purpose (1) To describe which equity-deserving populations have been the focus of reviews on clinical trial participation and which barriers, enablers, and strategies are relevant to them (2) to explore the extent to which PE and SDM are discussed in these reviews. Methods We searched for English-language reviews (including any study design) summarizing trial participation barriers, enablers, and/or strategies among equity-deserving populations in five peer-reviewed databases. We coded data on the (1) equity-deserving population(s) of focus, (2) barriers, enablers, or interventions/strategies mentioned, (3) PE reported, (4) Indigenous community engagement reported, and (5) SDM outcomes discussed. Results Findings from 100 reviews showed that some equity-deserving populations have been represented more than others (e.g., 76% on racially, ethnically, culturally, or linguistically diverse populations; 29% on sex and gender populations; 2% on educationally disadvantaged populations). More reviews described barriers (84%) than enablers (31%) or strategies to improve participation (69%). Forty-five reviews (45%) reported PE while 11 (11%) reported Indigenous community engagement. Many reviews (74%) mentioned SDM outcomes (i.e., 9/11 [81.8%] outcomes from Gillies et al.’s internationally agreed core outcome set); however, few reviews (29%) discussed SDM outcomes in detail. Conclusions Our findings suggest that PE and SDM could be more broadly applied among multiple equity-deserving groups to better serve disadvantaged communities. We advocate for an expanded focus on less-researched equity-deserving groups, improved PE reporting, prioritization of patient outcomes, and engagement with patients and Indigenous communities.

Plain English summary Background Many equity-deserving groups, such as people who experience structural barriers to health, face challenges with participating in clinical trials. These challenges can come from different levels, like personal, organizational, or system-wide barriers. Two approaches to support more inclusive participation are patient engagement (PE), i.e., working in partnership with patients and communities throughout the research process, and shared decision-making (SDM), i.e., helping people make informed choices that reflect their values and needs. Methods We conducted a review of reviews about equity-deserving groups participating in trials. We searched five scientific databases for published reviews in English. We coded data from the reviews using several established frameworks to see what helps or prevents equity-deserving groups from joining trials and how often PE and SDM were part of those studies. Results Of 100 reviews examined, most focused on racial, ethnic, cultural, or language diversity (76%) and sex or gender (29%). Few focused on education level (2%). Many reviews described barriers (84%), but fewer mentioned enablers (31%) or strategies (69%) to improve participation. Under half of reviews (45%) mentioned PE, 11 (11%) mentioned Indigenous community engagement. Many reviews mentioned SDM (74%), but few went into detail (29%). Conclusions Our results shows that some equity-deserving groups have been included in research about trial participation more than others. We recommend future research incorporate patient and community engagement, report it better, and focus on SDM to make trials even more inclusive.